This is a very simple equation. You can solve it both by the factorization method and by applying the quadratic equation.

Let's look at how we can solve it by factorization:

x

x

x(x+16)-4(x+16) = 0

(x-4)(x+16) = 0

x-4 = 0

or

x+16 = 0

x-4 = 0

x = 4

x+16 = 0

x = -16

So, x is equal to either 4 or -16. ----ANSWER

You can also solve this by applying the values into the quadratic formula. The quadratic formula is:

x=-b±√b

2a

Where, a=1

b=12

c=-64

Let's look at how we can solve it by factorization:

x

^{2}+12x-64 = 0x

^{2}+16x-4x-64 = 0x(x+16)-4(x+16) = 0

(x-4)(x+16) = 0

x-4 = 0

or

x+16 = 0

x-4 = 0

x = 4

x+16 = 0

x = -16

So, x is equal to either 4 or -16. ----ANSWER

You can also solve this by applying the values into the quadratic formula. The quadratic formula is:

x=-b±√b

^{2}-4ac2a

Where, a=1

b=12

c=-64